Legal Analysis of Tax Collection Implementation Through Forced Collection Letters - Tjandraningsih, Dewi (The International Journal of Law Review and State Administration, 2024)
This study aims to analyze the process of implementing tax collection through Forced Collection Letters at KPP Madya Tangerang in accordance with applicable legal regulations and identify the factors that hinder its successful execution. The research adopts an empirical juridical legal method. The findings indicate that the implementation of tax collection through Surat Paksa at the KPP Madya Tangerang has been conducted in a structured manner and adheres to the prevailing tax laws. However, several obstacles were identified in the process, which can be classified into three main factors: Law Enforcement Personnel: There is a shortage of law enforcement officers, particularly tax bailiffs, within the collection division. Facilities and Resources: The limited budget allocated by the government through the State Budget restricts the resources necessary for executing asset seizures effectively. Taxpayers: A significant issue is the inability to locate taxpayers, which hampers the delivery of information regarding outstanding tax arrears. This remains the most substantial challenge in the tax collection process.